2021
DOI: 10.24018/ejbmr.2021.6.6.1138
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cryptocurrency Price Index Using Artificial Neural Networks: A Survey of the Literature

Abstract: This paper initially presents a brief overview of the cryptocurrency and its history. We discuss the novel nature of literature attempting to create hybrid artificial neural network models to predict prices of cryptocurrency. For the remaining majority of the paper, we present the details of various hybrid artificial neural networks that have successfully been implemented to predict cryptocurrency prices in the form of a survey. Comparison of methods and results follow in the results section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…A feedforward MLPNN has three layers of input, interiors, and output 44 46 . MLPNN benefits from a unique training approach known as the backpropagation, and the utilized activation functions in this method are non-linear 47 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A feedforward MLPNN has three layers of input, interiors, and output 44 46 . MLPNN benefits from a unique training approach known as the backpropagation, and the utilized activation functions in this method are non-linear 47 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Stock market has always been a tremendous challenge for analysts due to its uncertain nature. Dase and Pawar (2010), Soni (2011), Budhani et al (2012), Vui et al (2013), Goel et al (2016), Murekachiro et al (2016), and Charandabi and Kamyar (2021) reviewed the implementation of ANN in stock market prediction. These studies found that ANN is the most suited predictor of stock market performance.…”
Section: Applications Of ML In Solving Dynamical Problemsmentioning
confidence: 99%
“…ANN as an alternative to statistical modeling and forecasting has been widely used today because, in some literature, it shows better performance when compared to the regression model [45,47,48]. In addition, ANN is also used to identify, model, and predict complex systems in various cases [49][50][51][52][53], including that was recently used to forecast cryptocurrency volatility [54,55]. To the best of our knowledge, no previous studies have used the ANN approach to model industrial energy demand and its relationship to subsector manufacturing output and climate change in Taiwan.…”
Section: Introductionmentioning
confidence: 99%